Genome-based reclassification of Azospirillum brasilense Az39 as the type strain of Azospirillum argentinense sp. nov. Issue 8 (1st August 2022) - dos Santos Ferreira, Natália; Coniglio, Anahí; Puente, Mariana; Sant'Anna, Fernando Hayashi; Maroniche, Guillermo; García, Julia; Molina, Romina; Nievas, Sofia; Volpiano, Camila Gazolla; Ambrosini, Adriana; Passaglia, Luciane M. P.; Pedraza, Raul O.; et al.
Abstract : Strain Az39 T of Azospirillum is a diazotrophic plant growth-promoting bacterium isolated in 1982 from the roots of wheat plants growing in Marcos Juárez, Córdoba, Argentina. It produces indole-3-acetic acid in the presence of l -tryptophan as a precursor, grows at 20–38 °C (optimal 38 °C), and the cells are curved or spiral-shaped, with diameters ranging from 0.5–0.9 to 1.8–2.2 µm. They contain C16 : 0, C18 : 0 and C18 : 1 ω 7 c / ω 6 c as the main fatty acids. Phylogenetic analysis of its 16S rRNA gene sequence confirmed that this strain belongs to the genus Azospirillum, showing a close relationship with Azospirillum baldaniorum Sp245 T, Azospirillum brasilense Sp7 T and Azospirillum formosense CC-Nfb-7 T . Housekeeping gene analysis revealed that Az39 T, together with five strains of the genus (Az19, REC3, BR 11975, MTCC4035 and MTCC4036), form a cluster apart from A. baldaniorum Sp245 T, A. brasilense Sp7 T and A. formosense CC-Nfb-7 T . Average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) between Az39 T and the aforementioned type strains revealed values below 96 %, the circumscription limit for the species delineation (ANI: 95.3, 94.1 and 94.0 %; dDDH: 62.9, 56.3 and 55.6 %). Furthermore, a phylogeny evaluation of the core proteome, including 809 common shared proteins, showed an independent grouping of Az39 T, Az19, REC3, BR 11975, MTCC4035 and MTCC4036. The G+C content in the genomic DNA of these six strains varied from 68.3 to 68.5 %. Based on the combined phylogenetic, genomic and phenotypic characterization presented here, we consider that strain Az39 T, along with strains Az19, REC3, BR 11975, MTCC4035 and MTCC4036, are members of a new Azospirillum species, for which the name Azospirillum argentinense sp. nov. is proposed. The type strain is Az39 T (=LBPCV39 T =BR 148428 T =CCCT 22.01 T ).